A polyvinyl acetal composition, interlayer and method of making and use thereof
Patent Information
- Application Number
- CN202611144342.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明的目的在于提供一种聚乙烯醇缩醛组合物、中间膜及其制备方法和应用,以解决现有含普通聚醋酸乙烯酯的聚乙烯醇缩醛中间膜在降低自着性时容易伴随相容性下降、雾度升高及湿热粘接稳定性不足的问题
1.本发明采用硅烷偶联剂改性聚醋酸乙烯酯作为聚乙烯醇缩醛树脂体系中的功能组分,能够有效降低中间膜表面粘附性,从而抑制卷材储存过程中的自着性。
Smart Images

Figure SMS_3 
Figure SMS_4 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer materials technology, specifically relating to a polyvinyl alcohol acetal composition, an intermediate membrane, its preparation method, and its application. Background Technology
[0002] Polyvinyl acetal resin, especially polyvinyl butyral resin, has good transparency, impact resistance, flexibility and adhesion to glass, and has been widely used as an interlayer material in laminated glass such as automotive safety glass, architectural laminated glass and photovoltaic encapsulation glass.
[0003] During the production, storage, and transportation of polyvinyl acetal interlayer film, the interlayer film is usually stored in roll form. Due to the direct contact between the film layers, self-adhesion, or self-attachment problem, is prone to occur, leading to difficulties in unwinding, film surface damage, and reduced processing efficiency. In severe cases, it can affect subsequent lamination processing and the quality of finished glass.
[0004] In the prior art, to reduce the self-adhesion of polyvinyl acetal interlayer films, a method of adding ordinary polyvinyl acetate to polyvinyl acetal resin has been proposed. For example, Japanese Patent Application Publication No. 2009-161584 discloses a polyvinyl acetal composition containing polyvinyl acetate (PVAc). By adding 0.1 to 50 parts by weight of ordinary PVAc to PVB resin, the interlayer adhesion can be reduced to a certain extent, eliminating the need for surface roughening or anti-sticking agent coating, thus simplifying the production process. However, this technical solution has the following inherent drawbacks: Firstly, the solubility parameters of ordinary PVAc and PVB resins differ significantly, resulting in limited compatibility. At high addition levels, macroscopic phase separation is likely to occur, leading to increased haze and decreased transparency of the film, which cannot meet the optical requirements of high-end automotive windshields. Secondly, ordinary PVAc is a non-reactive linear resin that can only be dispersed in the PVB matrix through physical entanglement. It cannot form chemical bonds with the glass interface. Under high temperature and high humidity conditions, the interfacial bonding strength is greatly reduced, and problems such as debonding, edge fogging, and resin migration and precipitation are prone to occur. Its long-term reliability is insufficient. Third, the entanglement between ordinary PVAc and PVB is weak, which makes it impossible to fix small molecule antioxidants and UV absorbers. During long-term use, the additives are prone to migration and precipitation, resulting in yellowing of the film and rebound of self-adhesion, making it unsuitable for long-term outdoor use. Fourth, while increasing the amount of PVAc improves the self-adhesion inhibition effect, it also significantly reduces the low-temperature penetration resistance and impact resistance of the PVB film, making it unable to meet the mandatory standard requirements for safety glass.
[0005] To address the aforementioned issues, the industry currently employs a physical blending method with PVAc and silane coupling agents to optimize interfacial adhesion. However, silane coupling agents are small molecules that are prone to migration and hydrolysis, and are susceptible to failure during storage, failing to fundamentally resolve the pain points of compatibility and long-term stability. Therefore, developing a PVB composition that can effectively suppress self-adhesion while also considering compatibility, interfacial stability, weather resistance, and mechanical properties is a pressing technical challenge for the industry. Summary of the Invention
[0006] The purpose of this invention is to provide a polyvinyl acetal composition, an intermediate film, a method for preparing the same, and its application, in order to solve the problems that existing polyvinyl acetal intermediate films containing ordinary polyvinyl acetate are prone to decreased compatibility, increased haze, and insufficient wet heat bonding stability when reducing self-adhesion.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a polyvinyl acetal composition comprising a polyvinyl acetal resin, a silane coupling agent-modified polyvinyl acetate, and a plasticizer. The present invention introduces reactive structural units derived from a silane coupling agent into polyvinyl acetate segments to form a silane-modified polyvinyl acetate, which is then dispersed as an anti-self-adhesion functional component in a polyvinyl acetal resin / plasticizer system.
[0008] The silane coupling agent-modified polyvinyl acetate is a random copolymer obtained by free radical copolymerization of vinyl acetate monomer and a silane coupling agent containing polymerizable double bonds. The silane grafting rate of the silane coupling agent-modified polyvinyl acetate is 0.5~5 mol%.
[0009] The silane grafting rate of silane-modified polyvinyl acetate was determined by 1H NMR spectroscopy. 1 The obtained spectrum was measured using 1H NMR, and baseline correction and peak integration were performed. The following characteristic peaks were integrated respectively: o Vinyl acetate unit: Acetyl methyl peak (-COOCH3, 3H) at δ=2.0ppm, the integrated area is denoted as A1; oγ-methacryloyloxypropyltrimethoxysilane (KH570) unit: methoxysilane peak (-Si (OCH3)3,9H) at δ=3.6ppm, the integrated area is denoted as A2; o-vinyltriethoxysilane (A151) unit: ethoxysilane peak (-Si(OCH2CH3)3,6H) at δ=3.8ppm, the integrated area is denoted as A2.
[0010] For KH570 modified PVAc, the grafting rate is calculated using the following formula: .
[0011] For A151-modified PVAc, the grafting rate is calculated using the following formula: .
[0012] By controlling the silane copolymer content to 0.5~5 mol%, a balance can be achieved between the glass interfacial interaction capability and the compatibility of the resin system. When the silane copolymer content is too low, the improvement on the wet heat adhesion retention performance is insufficient, while when it is too high, it is easy to lead to increased haze and decreased low temperature penetration resistance.
[0013] Preferably, in the polyvinyl acetal composition, the mass ratio of polyvinyl acetal resin, silane coupling agent modified polyvinyl acetate and plasticizer is 100:(0.1~50):(20~60).
[0014] More preferably, in the polyvinyl acetal composition, the mass ratio of polyvinyl acetal resin, silane coupling agent modified polyvinyl acetate and plasticizer is 100:(5~20):(20~60).
[0015] More preferably, in the polyvinyl acetal composition, the mass ratio of polyvinyl acetal resin, silane coupling agent modified polyvinyl acetate and plasticizer is 100:(6~12):(20~60).
[0016] Controlling the amount of silane-modified polyvinyl acetate relative to polyvinyl acetal resin to 6%~12% can reduce inter-film self-adhesion while maintaining the transparency, adhesion strength and low-temperature mechanical properties of the intermediate film.
[0017] Preferably, the number average molecular weight of the silane coupling agent modified polyvinyl acetate is 5,000 to 200,000.
[0018] More preferably, the number average molecular weight of the silane coupling agent modified polyvinyl acetate is 68,000 to 82,000.
[0019] The number average molecular weight of modified polyvinyl acetate is within the above range, which is beneficial for controlling the migration, dispersibility and melt processability of modified PVAc: if the molecular weight is too low, the functional components are more likely to migrate or precipitate; if the molecular weight is too high, the difficulty of melt blending and dispersion increases, which may cause phase separation or processing fluctuations.
[0020] Preferably, the glass transition temperature of the silane coupling agent modified polyvinyl acetate is 25~40 °C.
[0021] Controlling the glass transition temperature (Tg) of modified polyvinyl acetate within the above range is beneficial for its melt blending and dispersion stability in the polyvinyl acetal / plasticizer system. Too low a Tg may increase film surface tackiness, while too high a Tg may affect flexibility and low-temperature impact performance.
[0022] Preferably, the polyvinyl acetal resin comprises 8-25 wt% ethylene alcohol units and 0.1-15 wt% vinyl acetate units.
[0023] Preferably, the average degree of polymerization of the polyvinyl acetal resin is 150 to 3500.
[0024] Preferably, the degree of acetalization of the polyvinyl alcohol acetal resin is 60-85 mol.
[0025] Preferably, the polyvinyl acetal resin is one or more of polyvinyl butyral resin, polyvinyl acetal resin, polyvinyl isobutyral resin, and polyvinyl benzaldehyde resin.
[0026] Preferably, the silane coupling agent containing polymerizable double bonds includes at least one double bond structure selected from vinyl, acryloyloxy, or methacryloxy that can participate in free radical copolymerization.
[0027] More preferably, the silane coupling agent containing polymerizable double bonds is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropyltriethoxysilane.
[0028] Preferably, the plasticizer is one or more of triethylene glycol diisooctanoate, tetraethylene glycol diheptanoate, diisononyl adipate, dioctyl phthalate, and diisononyl 1,2-cyclohexanedicarboxylate.
[0029] Preferably, the composition further includes functional additives. The functional additives are one or more selected from antioxidants, ultraviolet absorbers, adhesion modifiers, antistatic agents, and flame retardants. The total amount of functional additives added does not exceed 5% of the amount of polyvinyl acetal resin used.
[0030] Preferably, the antioxidant is a hindered phenolic antioxidant.
[0031] In some embodiments, the antioxidant is antioxidant 1010.
[0032] Preferably, the ultraviolet absorber is a benzotriazole ultraviolet absorber.
[0033] In some implementations, the ultraviolet absorber is UV-326.
[0034] Preferably, the adhesive strength modifier is an alkali metal or alkaline earth metal organic acid salt.
[0035] In some embodiments, the adhesive strength modifier is one or more of magnesium acetate, potassium acetate, calcium acetate, magnesium propionate, magnesium butyrate, magnesium 2-ethylhexanoate, and potassium 2-ethylhexanoate.
[0036] Preferably, the antistatic agent is one or more of glyceryl monostearate, polyoxyethylene alkylamine, polyoxyethylene alkyl ether, sorbitan monostearate, polyether ester amide, and polyethylene glycol derivatives.
[0037] Secondly, the present invention also provides a method for preparing silane coupling agent modified polyvinyl acetate, comprising the following steps: Vinyl acetate monomer, silane coupling agent containing polymerizable double bonds, and organic solvent are added to a reaction vessel, heated to 50-80°C under an inert atmosphere, a free radical initiator is added, and the reaction is carried out for 4-12 hours. After the reaction is completed, unreacted monomer and organic solvent are removed to obtain silane coupling agent modified polyvinyl acetate.
[0038] Preferably, the organic solvent is methanol or ethyl acetate.
[0039] Preferably, the free radical initiator is azobisisobutyronitrile (AIBN) or benzoyl peroxide (BPO).
[0040] Preferably, the inert atmosphere is a nitrogen atmosphere.
[0041] Preferably, the removal of unreacted monomers and organic solvents is carried out by vacuum distillation.
[0042] More preferably, vacuum distillation includes a pre-solvent removal stage, a deep solvent removal stage, and a residual monomer removal stage.
[0043] Preferably, the temperature of the pre-solvent removal stage is 45~60℃, the absolute pressure is 20~40kPa, and the processing time is 0.5~2h.
[0044] Preferably, the temperature of the deep desolventizing stage is 65~80℃, the absolute pressure is 5~15kPa, and the processing time is 1~3h.
[0045] Preferably, the temperature for the residual monomer removal stage is 90~105℃, the absolute pressure is 0.5~2kPa, and the processing time is 0.5~2h.
[0046] More preferably, after the vacuum distillation is completed, the system is cooled to 35~45℃ before being discharged.
[0047] Thirdly, the present invention also provides a method for preparing a polyvinyl acetal composition, comprising the following steps: A premix is prepared by mixing polyvinyl acetal resin, silane coupling agent-modified polyvinyl acetate, plasticizer, and optional functional additives.
[0048] Preferably, the mixing is carried out in a high-speed mixer.
[0049] Preferably, the mixing temperature is 20~60 ℃ and the mixing time is 5~30 min.
[0050] More preferably, the speed of the high-speed mixer is 500~1200 rpm.
[0051] More preferably, the high-speed mixer rotates at 900 rpm.
[0052] Fourthly, the present invention also provides a polyvinyl acetal interlayer for laminated glass, which is obtained by melt extrusion molding of the polyvinyl acetal composition prepared above.
[0053] Preferably, the thickness of the intermediate film is 0.2~1.5 mm.
[0054] Preferably, melt extrusion molding includes the following steps: The premixed material is added to a twin-screw extruder and melt-blended at 150~220℃. It is then cast and extruded through a T-die, cooled and shaped by cooling rollers, drawn, and wound to obtain a polyvinyl acetal intermediate film.
[0055] Preferably, the screw speed of the twin-screw extruder is 250~350 rpm. The T-die temperature is 170~180 ℃. The cooling roller temperature is 15~30 ℃. The cooling roller linear speed is 0.6~1.2 m / min. The traction tension is 80~150 N / m.
[0056] In another aspect, the present invention also provides the application of the above-mentioned polyvinyl acetal composition or the above-mentioned polyvinyl acetal interlayer film for laminated glass in automotive safety glass, architectural laminated glass, photovoltaic encapsulation glass or flexible display folding glass.
[0057] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention uses silane coupling agent to modify polyvinyl acetate as a functional component in the polyvinyl alcohol acetal resin system, which can effectively reduce the surface adhesion of the interlayer film, thereby inhibiting the self-adhesion of the roll material during storage.
[0058] 2. The silane coupling agent modified polyvinyl acetate in this invention introduces silane-containing groups into the polyvinyl acetate molecular chain through free radical copolymerization, which makes it more dispersible and compatible in polyvinyl acetal resin, and reduces the risk of increased haze due to phase separation.
[0059] 3. The alkoxysilane structure derived from the silane coupling agent in this invention can undergo condensation or interfacial interaction with the hydroxyl groups on the glass surface under lamination and humid conditions, which is beneficial to improving the adhesion retention performance between the intermediate film and the glass, thereby improving the interfacial adhesion stability between the intermediate film and the glass, and is particularly beneficial to improving the adhesion retention performance under high temperature and high humidity environments.
[0060] 4. By controlling the silane grafting rate, the molecular weight of modified polyvinyl acetate and its addition amount, the present invention achieves a good balance between the self-adhesion, optical properties, adhesive properties, weather resistance and low-temperature impact resistance of the intermediate film.
[0061] 5. The composition of the present invention can be processed using an existing polyvinyl acetal intermediate film melt extrusion production line without the need for substantial modifications to existing equipment, making it suitable for industrial production. Detailed Implementation
[0062] To enable those skilled in the art to better understand the present application, the technical solutions in specific embodiments of the present application will be clearly and completely described below. Unless otherwise defined, the technical or scientific terms used in this invention should have the ordinary meaning understood by those skilled in the art.
[0063] Unless otherwise stated, all component contents are expressed in parts by weight.
[0064] All raw materials used in the embodiments and comparative examples of this invention are commercially available industrial-grade products, specifically including: PVB resin: 18 wt% vinyl alcohol unit content, 3 wt% vinyl acetate unit content, average degree of polymerization of 1700, degree of acetalization of 72 mol.
[0065] Ordinary PVAc: Number average molecular weight is 80,000, and glass transition temperature is 32 ℃.
[0066] Silane coupling agents: γ-methacryloyloxypropyltrimethoxysilane (KH570); vinyltriethoxysilane (A151).
[0067] Plasticizer: Triethylene glycol diisooctanoate (3GO).
[0068] Antioxidant: Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], also known as Antioxidant 1010.
[0069] Ultraviolet absorber: 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, i.e., UV-326.
[0070] Example 1 This embodiment provides a method for preparing silane-modified PVAc. Specifically, 100 parts of vinyl acetate monomer, 2 parts of KH570, and 200 parts of methanol are added to a reaction vessel, nitrogen is introduced to replace oxygen for 30 min, the temperature is raised to 65°C, 0.3 parts of AIBN are added, and the reaction is maintained at this temperature for 8 h.
[0071] After the reaction is complete, unreacted monomers and methanol are removed by vacuum distillation. Vacuum distillation includes the following stages: Pre-solvent removal stage: Keep warm for 1.5 h at a temperature of 50℃ and an absolute pressure of 30 kPa; Deep solvent removal stage: Under the condition of heating to 70℃ and gradually reducing the pressure to 10 kPa, the temperature is maintained for 2.5 h; Residual monomer removal stage: Under the conditions of heating to 95℃ and reducing the pressure to 1 kPa, hold at that temperature for 1.5 h.
[0072] After distillation, the material was cooled to 40 °C and discharged to obtain silane-modified PVAc, denoted as PVAc-1. This was used for membrane preparation in subsequent examples. Testing showed that PVAc-1 had a silane grafting rate of 1.2 mol%, a number-average molecular weight of 78,000, a glass transition temperature of 31 °C, a residual vinyl acetate monomer content of 420 ppm, and a total volatile matter content of 0.28%.
[0073] Example 2 This embodiment provides another method for preparing silane-modified PVAc, specifically by adding 100 parts of vinyl acetate monomer, 5 parts of KH570, and 200 parts of methanol to a reaction vessel, purging nitrogen to replace oxygen for 30 min, heating to 65°C, adding 0.3 parts of AIBN, and maintaining the temperature for 8 h.
[0074] After the reaction was completed, unreacted monomers and methanol were removed under the same vacuum distillation conditions as in Example 1 to obtain silane-modified PVAc, denoted as PVAc-2. The silane grafting rate was 2.8 mol%, the number-average molecular weight was 72,000, the glass transition temperature was 33°C, the residual vinyl acetate monomer was 380 ppm, and the total volatile matter was 0.25%.
[0075] Example 3 This embodiment provides a third method for preparing silane-modified PVAc. Specifically, 100 parts by weight of vinyl acetate monomer, 8 parts by weight of A151, and 200 parts by weight of ethyl acetate are added to a reaction vessel, nitrogen is introduced to replace oxygen for 30 min, the temperature is raised to 75°C, 0.4 parts by weight of BPO is added, and the reaction is maintained at this temperature for 6 h.
[0076] After the reaction is complete, unreacted monomers and ethyl acetate are removed by vacuum distillation. Vacuum distillation includes the following stages: Pre-solvent removal stage: Keep warm for 1 hour at a temperature of 55℃ and an absolute pressure of 35 kPa; Deep solvent removal stage: Under the condition of heating to 75℃ and gradually reducing the pressure to 12 kPa, the temperature is maintained for 2 h; Residual monomer removal stage: Under the conditions of heating to 100℃ and reducing the pressure to 1.5 kPa, hold for 1 h.
[0077] After distillation, the product was cooled to 40 °C and discharged to obtain silane-modified PVAc, designated PVAc-3. Analysis showed that the silane grafting rate was 3.5 mol%, the number-average molecular weight was 82,000, the glass transition temperature was 32 °C, the residual vinyl acetate monomer was 450 ppm, and the total volatile matter was 0.31%.
[0078] Example 4 This embodiment provides the preparation of a fourth type of silane-modified PVAc, specifically by adding 100 parts by weight of vinyl acetate monomer, 0.5 parts by weight of KH570, and 200 parts by weight of methanol to a reaction vessel, purging nitrogen to replace oxygen for 30 min, heating to 65°C, adding 0.3 parts by weight of AIBN, and maintaining the temperature for 8 h.
[0079] After the reaction was completed, unreacted monomers and methanol were removed under the same reduced pressure distillation conditions as in Example 1 to obtain silane-modified PVAc, denoted as PVAc-4. The silane grafting rate was 0.3 mol%, the number-average molecular weight was 81,000, the glass transition temperature was 31°C, the residual vinyl acetate monomer was 360 ppm, and the total volatile matter was 0.22%. The PVAc-4 prepared in this example is a modified PVAc system with a grafting rate lower than the lower limit of the grafting rate range claimed in this invention, and was used for the preparation of comparative examples.
[0080] Example 5 This embodiment provides the preparation of a fifth type of silane-modified PVAc, specifically by adding 100 parts by weight of vinyl acetate monomer, 10 parts by weight of KH570, and 200 parts by weight of methanol to a reaction vessel, purging nitrogen to replace oxygen for 30 min, heating to 65°C, adding 0.3 parts by weight of AIBN, and maintaining the temperature for 8 h.
[0081] After the reaction was completed, unreacted monomers and methanol were removed under the same reduced pressure distillation conditions as in Example 1 to obtain silane-modified PVAc, denoted as PVAc-5. The silane grafting rate was 5.5 mol%, the number-average molecular weight was 68,000, the glass transition temperature was 35°C, the residual vinyl acetate monomer was 400 ppm, and the total volatile matter was 0.27%. The PVAc-5 prepared in this example is a modified PVAc system with a grafting rate higher than the upper limit of the grafting rate range claimed in this invention, and was used for the preparation of comparative examples.
[0082] Examples 6-12 Examples 6-12 are examples of intermediate membrane preparation, wherein the composition formulations of each example are shown in Table 1, and the preparation methods of the intermediate membrane are the same: S1. According to the proportions shown in Table 1, add PVB resin, silane-modified PVAc, plasticizer 3GO, antioxidant 1010, and UV absorber UV-326 into a high-speed mixer and mix at 900 rpm and 30°C for 15 min to obtain a uniform premix. S2. Add the premixed material to a twin-screw extruder at a screw speed of 300 rpm and an extrusion temperature of 160~200℃. Extrude the material through a T-die at a die temperature of 180℃, and then cool and shape it through a 20℃ cooling roller at a linear speed of 0.6~1.2 m / min and a traction tension of 100 N / m. Then, traction and winding are performed to obtain a PVB intermediate film with a thickness of 0.76 mm.
[0083] Table 1: Composition formulations of Examples 6-12
[0084] Comparative Example 1 This comparative example is an intermediate membrane prepared using a conventional PVAc system.
[0085] Comparative Example 2 This comparative example serves as a blank control group for PVB resin.
[0086] Comparative Example 3 This comparative example is an intermediate membrane prepared by a physical blending system of ordinary PVAc and silane coupling agent.
[0087] Comparative Example 4 This comparative example is an intermediate film prepared using a modified PVAc system with a silane grafting rate lower than the lower limit of the scope of this invention.
[0088] Comparative Example 5 This comparative example is an intermediate film prepared from a modified PVAc system with a silane grafting rate higher than the upper limit of the scope of this invention.
[0089] The formulations for each comparative example are shown in Table 2 below. The preparation method of the intermediate membrane is the same as that in Example 6.
[0090] Table 2: Formulations of the compositions in Comparative Examples 1-5
[0091] Test case The test items and test methods are as follows: 1. Self-adhesion test: Two 100mm×100mm interlayer film samples were flatly stacked and subjected to a pressure of 0.1MPa at 23℃ and 50%RH for 24 hours. Subsequently, the T-shaped peel force was tested using a universal testing machine at a tensile speed of 50mm / min. The lower the peel force, the lower the self-adhesion of the interlayer film and the better the self-adhesion inhibition effect.
[0092] 2. Optical performance test: The visible light transmittance and haze of the intermediate film were tested in accordance with GB / T2410-2008 "Determination of transmittance and haze of transparent plastics".
[0093] 3. Interfacial adhesion test: The interlayer film was combined with two sheets of float glass with a thickness of 2 mm to form a 300 mm × 25 mm laminated glass sample; the 90° peel strength at 23°C was tested using a universal testing machine at a speed of 100 mm / min.
[0094] 4. Water boiling resistance test: Immerse a 100mm×100mm laminated glass sample in boiling water at 100℃ for 2 hours. After removing it, observe whether there are any phenomena such as edge opening, bubbles, fogging or delamination. If there are no abnormalities, it is recorded as qualified.
[0095] 5. Weather resistance test: A 1000-hour xenon lamp aging test was conducted according to GB / T16422.2-2014 "Laboratory Light Source Exposure Test Methods for Plastics - Part 2: Xenon Arc Lamp". The yellowing index YI before and after aging was tested and ΔYI was calculated.
[0096] 6. Low-temperature penetration resistance test: According to GB / T5137.3-2020 "Test methods for automotive safety glass - Part 3: Resistance to radiation, high temperature, humidity, combustion and simulated climate", the laminated glass sample is kept at -20℃ for 4 hours, and a 2260g steel ball is dropped freely from a height of 4m. If the glass is not penetrated, it is considered qualified.
[0097] The results of the above tests are summarized in the table below: Table 3: Performance Test Results
[0098] As shown in Table 3, Examples 6-12 all exhibited low self-peeling force while maintaining high visible light transmittance, low haze, good boiling stability, low yellowing, and satisfactory low-temperature penetration resistance. Examples 6-12 are generally superior to the conventional PVAc comparative examples in terms of optical performance, adhesive stability, weather resistance, and mechanical properties.
[0099] Comparative Example 1 uses ordinary PVAc. Although the self-adhesive peeling force is reduced, the haze is significantly increased. After boiling in water, the edges open. The xenon lamp aging ΔYI increases, indicating that the compatibility and interfacial stability of ordinary PVAc with PVB are insufficient.
[0100] Comparative Example 2, which does not contain PVAc or has modified PVAc, has a self-adhesion peel force of 28.6 N / 100mm, indicating that the interlayer film has severe self-adhesion when no anti-self-adhesion functional component is added.
[0101] Comparative Example 3, which uses a physical blend of ordinary PVAc and KH570, showed high levels of haze and yellowing, and slight fogging after boiling in water, indicating that the physical addition of small molecule silane coupling agents is difficult to maintain a stable effect over a long period of time.
[0102] In Comparative Example 4, the silane-modified PVAc-4 had a silane grafting rate of less than 0.5 mol%, resulting in limited improvement in interfacial adhesion and slight edge splitting after boiling. In Comparative Example 5, the silane-modified PVAc-5 had a silane grafting rate of more than 5 mol%, leading to increased haze and failure to meet low-temperature penetration resistance standards. This indicates that an excessively high silane grafting rate can negatively impact the balance between compatibility and mechanical properties. Therefore, limiting the silane grafting rate to 0.5–5 mol% can balance self-adhesion suppression, optical properties, adhesion stability, and mechanical properties.
[0103] Finally, it should be noted that the described embodiments are merely some, not all, of the embodiments of the present invention. Those skilled in the art will understand that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the claims and their equivalents; that is, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
Claims
1. A polyvinyl acetal composition, characterized in that, It includes polyvinyl alcohol acetal resin, silane coupling agent modified polyvinyl acetate, and plasticizer in a mass ratio of 100:(0.1~50):(20~60); Among them, silane coupling agent modified polyvinyl acetate is a random copolymer obtained by free radical copolymerization of vinyl acetate monomer and silane coupling agent containing polymerizable double bonds, and its silane grafting rate is 0.5~5 mol.
2. The polyvinyl acetal composition according to claim 1, characterized in that, The polyvinyl acetal composition includes polyvinyl acetal resin in a mass ratio of 100:(5~20):(20~60), silane coupling agent modified polyvinyl acetate, and plasticizer.
3. The polyvinyl acetal composition according to claim 1, characterized in that, Polyvinyl acetal resin comprises 8-25 wt% ethylene alcohol units and 0.1-15 wt% vinyl acetate units; and the average degree of polymerization of polyvinyl acetal resin is 150-3500.
4. The polyvinyl acetal composition according to claim 3, characterized in that, The degree of acetalization of polyvinyl alcohol acetal resin is 60~85 mol%, and the acetalizing agent used is one or more of acetaldehyde, n-butyraldehyde, isobutyraldehyde, and benzaldehyde.
5. The polyvinyl acetal composition according to claim 1, characterized in that, The polymerizable double bond silane coupling agent is one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropyltriethoxysilane.
6. The polyvinyl acetal composition according to claim 1, characterized in that, The plasticizer is one or more of the following: triethylene glycol diisooctanoate, tetraethylene glycol diheptanoate, diisononyl adipate, dioctyl phthalate, and diisononyl 1,2-cyclohexanedicarboxylate.
7. The polyvinyl acetal composition according to claim 1, characterized in that, It also includes functional additives, which are one or more of antioxidants, ultraviolet absorbers, adhesion modifiers, antistatic agents, and flame retardants; the total amount of functional additives used shall not exceed 5% of the amount of polyvinyl acetal resin used.
8. A polyvinyl acetal interlayer film, characterized in that, The polyvinyl acetal composition according to any one of claims 1 to 7 is obtained by melt extrusion molding, wherein the thickness of the polyvinyl acetal intermediate film is 0.2 to 1.5 mm.
9. A method for preparing the intermediate membrane according to claim 8, characterized in that, Includes the following steps: S1, polyvinyl alcohol acetal resin, silane coupling agent modified polyvinyl acetate, plasticizer and optional functional additives are mixed to obtain a premix; S2, the premixed material is melt-blended, then extruded through a T-die, cooled and shaped, drawn and wound to obtain a polyvinyl acetal interlayer for laminated glass.
10. The application of a polyvinyl acetal interlayer in laminated glass, characterized in that, The polyvinyl acetal interlayer is the interlayer as described in claim 8.
Citation Information
Patent Citations
Polyvinyl acetal composition containing polyvinyl acetate, polyvinyl acetal sheet comprising the polyvinyl acetal composition, and interlayer film for laminated glass comprising the polyvinyl acetal composition
JP2009161584A